2020
DOI: 10.1371/journal.pntd.0008136
|View full text |Cite
|
Sign up to set email alerts
|

Understanding risk communication for prevention and control of vector-borne diseases: A mixed-method study in Curaçao

Abstract: BackgroundRisk communication (RC) is an essential tool for the prevention and control of diseases as it impacts risk perception, increases awareness and might change behaviour. It is the interactive exchange of information about risks among experts and people. Effective RC can minimize the impact that diseases such as dengue, chikungunya and Zika have on populations. This study aimed to understand RC regarding vector-borne diseases in its social context and from the viewpoint of the audience to strengthen RC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Qualitative methods were used to (a) understand how risk was communicated during the dengue, chikungunya, and Zika virus infection epidemics, (b) compare the content of newspapers with the perceptions of locals and experts/ government officials, and (c) explore the influence of trust and heuristics on risk perception. This study's results concerning the channels of information are in concordance with the findings of a recent study conducted in Curaçao (Mulderij-Jansen et al, 2020) and Jamaica (Shuaib et al, 2010). In Jamaica, investments have been made in media campaigns concerning dengue virus infection; however, an assessment to determine the impact of such interventions has not been conducted.…”
Section: Discussionsupporting
confidence: 92%
“…Qualitative methods were used to (a) understand how risk was communicated during the dengue, chikungunya, and Zika virus infection epidemics, (b) compare the content of newspapers with the perceptions of locals and experts/ government officials, and (c) explore the influence of trust and heuristics on risk perception. This study's results concerning the channels of information are in concordance with the findings of a recent study conducted in Curaçao (Mulderij-Jansen et al, 2020) and Jamaica (Shuaib et al, 2010). In Jamaica, investments have been made in media campaigns concerning dengue virus infection; however, an assessment to determine the impact of such interventions has not been conducted.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, office workers might have higher level of education which was one of the associated factors for better knowledge on MBDs as shown in our qualitative result of health staff and other studies [16,18,24,32,35]. One study in Curaçao also found a positive association of level of education with the increase of accessing information on MBDs [37].…”
Section: Discussionsupporting
confidence: 67%
“…Correspondingly, H3 validated the standpoint of the risk perception attitude framework and provided further clarification in that when individuals have reduced perception of risks, attitude change can occur, which can lead towards acceptance of GMF usage [ 87 , 88 ]. Past theories, such as social amplification of risk theory (SART), attempted to relate societal factors and people’s procedural assessment of risks [ 68 ]. SART suggested that people’s societal response structure can outline their understanding of risks.…”
Section: Discussionmentioning
confidence: 99%
“…In the instance of GMF product usage, the consequences connected with consuming them are generally vague among common people as both harmful and expedient consequences can be found in national and international media about innovative products [ 67 ]. In general, a common person can have more uncertainties about the adoption of such innovative products based on the uncertain attitudes formed because of unknown or dreaded outcomes related to health or environmental concerns [ 68 ]. However, SLM argues that by providing objective knowledge or educating the common person through informed and relevant persons, such as experts, people can become aware of accurate and reliable information [ 40 ].…”
Section: Literature Review and Theoretical Underpinningmentioning
confidence: 99%